Respostas
respondido por:
0
= (x² + 2xy + y²) + (3x² - 2xy + 4x²)
= x² + 2xy + y² + 3x² - 2xy + 4x²
= x² + 3x² + 4x² + 2xy - 2xy + y²
= 8x² + y²
= x² + 2xy + y² + 3x² - 2xy + 4x²
= x² + 3x² + 4x² + 2xy - 2xy + y²
= 8x² + y²
respondido por:
1
= (x² + 2xy + y²) + (3x² - 2xy + 4x²)
= x² + 2xy + y² + 3x² - 2xy + 4x²
= x² + 3x² + 4x² + 2xy - 2xy + y²
= 8x² + y²
= x² + 2xy + y² + 3x² - 2xy + 4x²
= x² + 3x² + 4x² + 2xy - 2xy + y²
= 8x² + y²
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás